The effects of core muscle strengthening training on flexibility, strength and driver shot performance in female pro-golfer - Kim, K. J. (International Journal of Applied Sports Sciences, 2010)
The purpose of this study is to investigate the effect of 12 weeks` combined training in core muscle strengthening on the flexibility, muscular strength, and driver shot performance of the core body parts of the female professional golfers. Subjects were members of the Korea Ladies Professional Golf Association. They were divided into two groups (of whom 9 belonged to the training group, and 8 belonged to the control group). Changes in flexibility (forward flexion and back flexion), maximal muscular strength (back extension and squat), isometric strength (back strength), and core muscle and driver shot performance (ball speed, clubhead speed, and carry distance) were measured before and after 12 weeks' combined training. The results were as follows: in physical fitness parameters, back flexion and maximal strength of back extension and squat increased significantly in training group following 12 weeks' core muscle strengthening training. In driver shot performance, clubhead speed and carry distance increased significantly in training group following 12 weeks' core training. The findings of the present study showed 12 weeks' combined core muscle training had positive effects on flexibility and strength of core muscle. Moreover, it was effective in enhancing driver shot performance in female professional golfers. This suggests that application of specific and scientific core muscle training should be done continuously in female professional golfers.